(3QSGdI GdTcd hGdceGds - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdSOb hGdMGce HGdMb GdeYHhO HdZGJ LejY GdNdb s
(3BNQgG (B:s
(3hGcTa eG cfJ JVeQg hJSJQg aeG Ydi GdQShd GdfGUM Shi GdHdGZ GdeHjf JeJ QSGdI GdgfO HMeO Gdehdi hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B61s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis